Exploring Community Creation: Conversations of Young Black Women - Ngandi, Asemahle (University of Cape Town, 2024)
In order to showcase the significance of the often-trivialised act of women talking to each other, the purpose of this research project was to explore how young black women use talking to create community with each other. The purpose of this research is to explore how young black South African women talking to each other, having conversations with each other, work to create bonds and ultimately community with each other – or, in bell hooks' (2000) terms, a Sisterhood. This act of women talking – black women, no less – to each other goes against the grain, it is a revolutionary act that they have been conditioned against precisely because of its revolutionary nature and because of the power that lies in the unpredictability of it. Along with staying silent, women are conditioned into not having bonds or relationships with each other because they are natural enemies, because all that would come from such relations would be unimportant, because they would tear each other down – as such, women cannot and should not bond with each other (hooks; 2000:43). This is reflected in the literature, particularly literature on Africa. The literature available on the socio-linguistic study of language and language varieties is expansive on the embodiment of these varieties by young African men. This solidifies the notion that [young African] women are not talking – not to young men, not to each other, not to anyone. Due to the COVID-19 induced travel restrictions, the research used virtual ethnography principles applied to past synchronous one-one-one WhatsApp chats to collect data. Using a Speech Act Analysis on the emojis used in the chats, it was discovered that these play various roles in these conversations, including mitigating serious conversations, to contextualise seemingly negative messages and to convey emotions between the interlocutors. Additionally, focussing on and analysing the code switches that occurred in the conversations revealed that switches were also used to provide comedic relief in heavy conversations and/or to make the other person laugh and code switches did friendship maintenance work. From the WhatsApp conversations, one can therefore deduce that these young black women's use of language and linguistic matter – albeit in a virtual space – play an important role in creating community in that both emojis and code switches insist on the fragility of the people in conversation and create a community that not only accommodates this fragility, but one that allows and accepts it.